KESESUAIAN ASESMEN BUATAN GURU DENGAN SILABUS KURIKULUM 2013 - Nofika Kartika Dewi; Johanes Djoko Budiono; Muji Sri Prastiwi (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
This research aimed to describe suitability between assessment made by Biology teacher of 10th grade with the Syllabus. The kind of this research was descriptive. The subject of this research was Biology teacher at Senior High School in Ponorogo Regency. The source of this research was the teacher’s lesson plan and the responses in teacher’s questionnaire. The data collecting techniques were questionnaire and documentation. The data analysis was descriptive percentage. Based on the data analysis are known that assessment made by Biology teacher of 10th grade in the first semester is categorized less in accordance with the Syllabus. Keywords: assessment, Kurikulum 2013